Monoallelic TYROBP deletion is a novel risk factor for Alzheimer’s disease - Henna Martiskainen; Roosa-Maria Willman; Päivi Harju; Sami Heikkinen; Mette Heiskanen; Stephan A. Müller; Rosa Sinisalo; Mari Takalo; Petra Mäkinen; Teemu Kuulasmaa; Viivi Pekkala; Ana Galván del Rey; et al. (Molecular Neurodegeneration)
Abstract Biallelic loss-of-function variants in TYROBP and TREM2 cause autosomal recessive presenile dementia with bone cysts known as Nasu-Hakola disease (NHD, alternatively polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy, PLOSL). Some other TREM2 variants contribute to the risk of Alzheimer’s disease (AD) and frontotemporal dementia, while deleterious TYROBP variants are globally extremely rare and their role in neurodegenerative diseases remains unclear. The population history of Finns has favored the enrichment of deleterious founder mutations, including a 5.2 kb deletion encompassing exons 1–4 of TYROBP and causing NHD in homozygous carriers. We used here a proxy marker to identify monoallelic TYROBP deletion carriers in the Finnish biobank study FinnGen combining genome and health registry data of 520,210 Finns. We show that monoallelic TYROBP deletion associates with an increased risk and earlier onset age of AD and dementia when compared to noncarriers. In addition, we present the first reported case of a monoallelic TYROBP deletion carrier with NHD-type bone cysts. Mechanistically, monoallelic TYROBP deletion leads to decreased levels of DAP12 protein (encoded by TYROBP) in myeloid cells. Using transcriptomic and proteomic analyses of human monocyte-derived microglia-like cells, we show that upon lipopolysaccharide stimulation monoallelic TYROBP deletion leads to the upregulation of the inflammatory response and downregulation of the unfolded protein response when compared to cells with two functional copies of TYROBP. Collectively, our findings indicate TYROBP deletion as a novel risk factor for AD and suggest specific pathways for therapeutic targeting.